Selective photorelease of model amino acids from coumarin ester conjugates - Piloto, Ana M. (2012)
There is a strong interest in the design of more efficient protecting groups that allow orthogonal cleavage/deprotection for application with biomolecules, by rapid and clean cleavage under irradiation at wavelengths that are not detrimental to biological systems, with spatial and temporal resolution.1 Coumarin derivatives are well established photolabile protecting groups that have been used in the caging of various functional groups (such as alcohols, amines, phosphates, aldehydes, ketones and carboxylic acids),2 whereas benzocoumarin derivatives were reported for the first time by us as carboxyl protecting groups cleavable by light and with sensitivity to two-photon excitation.3 In this communication, we present the synthesis of model amino acid conjugates, namely glycine, alanine, valine and phenylalanine, based on coumarin and benzocoumarin, with the aim of assessing the selectivity of photolytic removal. Photolysis studies were carried out under irradiation at different wavelengths (250, 300, 350 and 419 nm) in a Rayonet RPR-100 photochemical reactor in acetonitrile/HEPES buffer solution (80:20). It was found that, in some cases, the cleavage of the ester bond between the heterocycle and the model amino acids occurred in very different irradiation times at the same irradiation wavelength, enabling the selective removal of one heterocycle in the presence of the other heterocycle. These results opens up the possibility of considering coumarin and benzocoumarin as a protecting group pair for the protection of a bifunctional molecule through ester bonds.